Notification of crop varieties and registration of germplasm - Agrawal, P. K. (The Indian Journal of Genetics and Plant Breeding, 2016)
Vivek Dhan 157 (VL 8302) is a June sown rainfedupland rice (Oryza sativa L.) variety developed by theVivekananda Parvatiya Krishi Anusandhan Sansthan,Almora. It is derived from the cross VR 9588/A-57. Itwas recommended for release by the ‘VarietyIdentification Committee’ held on April 6th, 2014 atthe Directorate of Rice Research, Hyderabad duringthe 49th Annual Rice Research Group Meeting for thelow elevated hills of Meghalaya and mid-hills ofUttarakhand. It was released and notified by the CentralSub-committee on Crop Standards vide notificationnumber SO 1543 dated 31th July 2014 for cultivationin the low elevated hills of Meghalaya and mid-hills ofUttarakhand. Farmers from different hill states wouldcertainly prefer this variety because of high grain yield,resistance against blast, high HRR and grain quality.The specific area of its adaptation of this variety isthe rainfed kharif, both under high and low fertility inthe Northern hills of Uttarakhand and Meghalaya.